2022
DOI: 10.1111/aas.14100
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in intensive care patients: Incidence, time course, and risk factors

Abstract: Background Acute kidney injury (AKI) is frequent and influences the prognosis of intensive care unit (ICU) patients. The aim of this study was to estimate the incidence, time‐course, risk factors, and mortality of AKI among unselected ICU patients. Methods All adult ICU patients admitted to the ICU at the University Hospital in Central Norway from 2010 to 2015 with a stay of 24 h or more were included in the study. AKI was defined according to the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
(46 reference statements)
1
6
2
1
Order By: Relevance
“…This could be attributed to the development of liver injury (20.0% vs 6.7%) and the occurrence of acquired infections during the patient's stay. 27,28 In contradiction to our findings, Benjamin et al reported four cases of anemic COVID-19 patients, two were critically ill, and all four patients received EPO analogs, changes from baseline hemoglobin and hematocrit were variable. However, it is good to note that the four patients were smokers in addition to one patient with CKD, which subsequently suggests possible ESA administration pre-COVID-19 infection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the development of liver injury (20.0% vs 6.7%) and the occurrence of acquired infections during the patient's stay. 27,28 In contradiction to our findings, Benjamin et al reported four cases of anemic COVID-19 patients, two were critically ill, and all four patients received EPO analogs, changes from baseline hemoglobin and hematocrit were variable. However, it is good to note that the four patients were smokers in addition to one patient with CKD, which subsequently suggests possible ESA administration pre-COVID-19 infection.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be attributed to the development of liver injury (20.0% vs 6.7%) and the occurrence of acquired infections during the patient's stay. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this nding is lower than the studies conducted in Norway (53.5%) [22], Jordan (31.6%) [23], Iran (37%) [32], Indonesia (43%) [20], Brazil (40.5%) [33], Uruguay(50.1%) [17], Zambia(52.9%) [7] and Sudan (39%) [9]. The reason for this discrepancy might be due to the difference in the characteristics of study population, sampling method, level of study setting, duration of follow-up time, and sample size.…”
Section: Discussioncontrasting
confidence: 75%
“…According to the different studies conducted around the world age greater than sixty, male gender, hypertension, diabetes mellitus, chronic cardiovascular disease, stroke, sepsis, shock, anemia, hypotension, acute respiratory distress syndrome(ARDS), coronary artery disease, and oncologic disease, Human immunode ciency virus (HIV), trauma, major abdominal surgery, high serum creatinine concentration, low platelet level, urea, treatments of ; diuretics, angiotensive converting enzyme inhibitors(ACEIs), non-steroidal anti-in ammatory, gentamicin, and vasopressor drugs, oliguria, low blood pressure, low Glasgow Coma Scale(GCS), high respiration rate, hypoxia, hyperthermia, serum potassium abnormality, and serum sodium abnormality were independent predictors of AKI among patients admitted to intensive care unit [6,7,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, ARDS patients presented a variety of comorbidities (e.g., hypertension, congestive heart failure, and diabetes mellitus), which accounted for renal vulnerability (49,50). The crosstalk between the kidney and heart is also important, and patients with congestive heart failure and hypertension tend to experience AKI due to decreased renal perfusion (51,52). Diabetes mellitus was reported as an independent indicator for postoperative AKI due to increased susceptibility to renal ischemia and reperfusion injury (53).…”
Section: Discussionmentioning
confidence: 99%